Sustainable production and characterization of microalgae using aquaponics system for biofuel application - Yong, Jia Hong (2017)
This thesis consists microalgae production using aquaponics system. Building of this system involves the piping and connection to integrate several components. It starts with the fish tank where fish were to be fed and secrete wastes into the water. The waste water then pumped up to the hydroponic tank containing hydroton, or known as clay balls for microbes and plants attachment. The waste water should be converted to nutrient water by nitrogen-fixing bacteria and directed (drained) to other tank for microalga culture. Lastly, the water flow now will pass through a filter cartridge to harvest algae and giving clean water back to the aquarium. In term of characterization of microalgae, firstly the growth of microalgae are determined using spectrophotometric and gravimetric analysis. Specific growth rate of microalgae in aquaponics system I can reach up to 0.127g of wet mass/day, or 0.141g of dry mass/day and 0.14 absorbance value/day. As compared to system I, system II achieved relatively higher rate, with 0.171g of wet mass/day, 0.194g of dry mass/day or 0.145 absorbance value/day. Throughout this research, microalgae were harvested 3 times, at the 21 day, 35th day and 77th day, and the highest microalgae biomass productivity calculated for system I and II are 0.0799g/L of culture per day and 0.1095g/L of culture per day respectively. Besides that, microscopic identification of microalgae species present in the culture by referring to available literature sources. Some dominant species present in the sample microalgae population identified are Desmodesmus sp., Micractimium sp., Chlorella sp., Staurodesmus sp., Coelosphaerium sp.; and Frustulia sp. On the other hands, for the biofuel application, conventional liquid-liquid extraction with chloroform-methanol was used to extract microalgal lipid, the highest total lipid obtained in the experiment was 21.73% and 18.82% for system I and II respectively. Then, the production of FAME, using alkali-catalysed transesterification are quantified and analyzed using GC-MS. The most abundant FAME biofuel analyzed was methyl formate and acetic acid methyl ester, with up to 9.03% of peak area. Lastly, the biofuel yield calculated was 3692.08g/hectare and 4646.37g/hectare for system I and II respectively. In addition, nile red staining technique was also used to obtain the fluorescence intensity for microalgae lipid quantification. The lipid concentration recorded was 749.50mg/1 and 3389.77mg/1 for system I and II respectively.